The Effect of Resilience on Students’ Mathematical Logical Thinking Ability - Yuliana, Dita Indah; Muhammad Aziz, Irsyad (International Journal of Research in Mathematics Education, 2025)
The ability to think logically is one of the essential skills acquired through learning mathematics, as it facilitates students in understanding material and solving problems in a rational manner. However, students often avoid working on mathematics problems due to the belief that mathematics is inherently difficult. To address this issue, students must develop positive attitudes such as self-confidence, persistence, perseverance, and optimism—traits closely related to resilience. This study aimed to examine the influence of mathematical resilience on students’ logical thinking ability in mathematics among eighth-grade students at SMP Negeri 2 Kutasari. This research employed a quantitative approach using a survey method. The population consisted of all eighth-grade students at SMP Negeri 2 Kutasari, totaling 219 students. A sample of 142 students was selected using the Slovin formula and simple random sampling technique. The research instruments included a resilience questionnaire and a logical thinking ability test. Data were analyzed using simple linear regression analysis. The results showed that mathematical resilience had a significant effect on students’ mathematical logical thinking ability. The coefficient of determination was 0.058, indicating that 5.8% of the variance in logical thinking ability was explained by resilience, while the remaining 94.2% was influenced by other variables not examined in this study.